Tree-based restoration of the floristic and genetic diversity of tropical dry forest - Thomas, E.; Alcázar, C.; Beltrán, M.; Amaya, K.; Bioversity International (2014)
In South America, 60% of the original TDF ecosystem coverage has disappeared and in Colombia only 8% of its original cover stands. Remaining forest patches are very fragmented, immersed in landscapes dominated by crops and pasture. Ecosystem restoration is considered a global priority to contribute to biodiversity conservation, climate change mitigation and adaptation, and to combat desertification. To ensure the success of restoration initiatives requirements must focus on the choice and combination of tree species and the genetic quality of the germplasm used. Our goal is to develop best practices and successful protocols for tree-based ecological restoration of TDF in Colombia taking into account genetic considerations, species functional traits and expected impacts of climate change. Since protocols will be developed using secondary data and geospatial and ecological modeling techniques, they will be validated by field studies and experiments at sites across the country, with a strong focus on the compensation area for biodiversity loss caused by the construction of the largest water dam in Colombia, the hydroelectric of Ituango.